Emergency remote teaching and students’ academic performance in higher education during the COVID-19 pandemic: A case study - Iglesias-Pradas, Santiago; Hernández-García, Ángel; Chaparro-Peláez, Julián; Prieto, José Luis (Computers in human behavior, 2021)
The COVID-19 pandemic has caused a massive disruption in the way traditional higher education institutions deliver their courses. Unlike transitions from face-to-face teaching to blended, online or flipped classroom in the past, changes in emergency remote teaching –a temporary shift of instructional delivery to an alternate remote delivery mode due to crisis circumstances– happen suddenly and in an unplanned way. This study analyzes the move to emergency remote teaching at the School of Telecommunication Engineering (Universidad Politécnica de Madrid), and the impact of organizational aspects related to unplanned change, instruction-related variables –class size, synchronous/asynchronous delivery– and use of digital supporting technologies, on students' academic performance. Using quantitative data of academic records across all (N = 43) courses of a bachelor's degree programme in Telecommunication Engineering and qualitative data from a questionnaire delivered to all (N = 43) course coordinators, the research also compares the academic results of students during the COVID-19 pandemic with those of previous years. The results of this case study show an increase in students' academic performance in emergency remote teaching, and support the idea that organizational factors may contribute to successful implementation of emergency remote teaching; the analysis does not find differences across courses with different class sizes or delivery modes. The study further explores possible explanations for the results of the analysis, considering organizational, individual and instruction-related aspects.